Hard carbon negative electrode material and preparation method and application thereof

The hard carbon negative electrode material is prepared by two-stage crosslinking and carbonization treatment starch, which solves the problems of low sodium storage capacity and insufficient first-term effect of the negative electrode material of hard carbon sodium ion battery, and achieves high-capacity and high-term effect of hard carbon negative electrode material. Improves the performance of sodium ion batteries.

CN119306199AActive Publication Date: 2025-01-14HUNAN SHINZOOM TECH

Patent Information

Application Number
CN202310854032.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-14
Estimated Expiration
2043-07-12

AI Technical Summary

Technical Problem

The existing negative electrode materials for hard carbon sodium ion batteries have problems such as low sodium storage capacity, low first efficiency and insufficient long cycle performance, which limits the development and commercial application of sodium ion batteries.

Method used

Using starch as raw material, a hard carbon negative electrode material with rich nanopores was prepared through two-stage cross-linking pretreatment and carbonization treatment. The nanopores consist of open pores and closed pores, with a diameter of 0.8-2.5nm, and the open pores are Hard carbon anode material with an ore diameter of ≤0.4nm.

Benefits of technology

It realizes a hard carbon negative electrode material with high capacity and high first-time efficiency, enhances the storage capacity of sodium ions and improves the performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306199A_ABST
    Figure CN119306199A_ABST
Patent Text Reader

Abstract

The invention discloses a hard carbon negative electrode material and a preparation method and application thereof, and belongs to the technical field of batteries. Comprising the following steps: by taking starch as a raw material, carrying out cross-linking treatment on starch particles by using a first cross-linking agent, controlling the cross-linking degree of the starch particles, enabling a starch skeleton to be in a semi-fixed state, maintaining the original morphology of the starch particles, giving a certain shrinkage cavity space for two-section cross-linking, and then treating by using a second cross-linking agent to shrink the pore structure of the starch, so as to obtain the modified starch. The preparation method comprises the following steps: carrying out cross-linking on starch-based hard carbon so as to achieve the purpose of adjusting pores, finely regulating the pore structure of the starch-based hard carbon, and carbonizing cross-linked starch particles obtained by cross-linking, thereby obtaining the hard carbon negative electrode material with better sodium storage performance, high capacity and high first efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a hard carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries are gaining more and more attention from the market due to their advantages such as high resource abundance and low cost. However, compared with lithium ions, the radius of sodium ions is more than 35% larger, and sodium ions cannot be embedded in the graphite interlayer to form thermodynamically stable Na-C compounds with graphite. Therefore, the mainstream graphite anode in lithium-ion batteries cannot meet the requirements of sodium-ion battery anodes. Soft carbon is one of the candidate materials for sodium-ion battery anode materials, but soft carbon only has a slope sodium storage capacity, a high sodium storage potential, and the sodium storage capacity of soft carbon is difficult to exceed 300mAh / g, which is not an ideal choice for sodium-ion battery anode materials. Compared with soft carbon, the sodium storage capacity of hard carbon consists of slope area capacity and platform area capacity, the average sodium storage potential is low, and the theoretical sodium storage capacity of hard carbon can be as high as 550mAh / g. Therefore, hard carbon is the mainstream choice for sodium-ion battery anode materials. However, the existing hard carbon sodium-ion battery anode materials still have disadvantages such as low specific capacity, low first efficiency, and insufficient long-cycle performance, which seriously restricts the development and commercial application of sodium-ion batteries. Summary of the invention

[0003] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a hard carbon negative electrode material and a preparation method and application thereof.

[0004] The present invention solves the technical problem by adopting the following technical solutions.

[0005] The invention provides a method for preparing a hard carbon negative electrode material, comprising: using starch as a raw material, subjecting starch particles to a two-stage cross-linking pretreatment, and then subjecting the starch particles to a carbonization treatment to obtain the hard carbon negative electrode material.

[0006] The present invention also provides a hard carbon negative electrode material, which has abundant nanopores, and the nanopores are composed of open pores and closed pores, and the pore diameters of the open pores and the closed pores are both 0.8-2.5nm, and the pore diameter of the open pores is ≤0.4nm.

[0007] The present invention also provides a sodium ion battery, wherein the negative electrode of the sodium ion battery comprises the hard carbon negative electrode material.

[0008] The present invention has the following beneficial effects:

[0009] The present invention provides a hard carbon negative electrode material and a preparation method and application thereof. Starch is used as a raw material, and starch particles are subjected to a two-stage crosslinking pretreatment and a carbonization treatment to obtain a hard carbon negative electrode material. The starch is crosslinked in two stages to control the degree of crosslinking, so as to achieve fine regulation of the microstructure of the crosslinked starch, and finally a hard carbon negative electrode material with abundant nanopores is obtained. The abundant pore structure enhances the storage capacity of sodium ions, and the nanopores on the hard carbon negative electrode material are composed of open channels and closed channels, and the pore diameters of the open channels and the closed channels are both 0.8-2.5nm, and the pore diameter of the open channels is ≤0.4nm. The obtained hard carbon negative electrode material has the advantages of both high capacity and high initial efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0011] Figure 1 This is the SEM image of the hard carbon sample that has not been crushed in Example 3. 。

[0012] Figure 2 This is the charge and discharge curve of the hard carbon sample in Example 3. DETAILED DESCRIPTION

[0013] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0014] A hard carbon negative electrode material and a preparation method and application thereof provided in an embodiment of the present invention are specifically described below.

[0015] In a first aspect, an embodiment of the present invention provides a method for preparing a hard carbon negative electrode material, comprising: using starch as a raw material, subjecting starch particles to a two-stage crosslinking pretreatment and a carbonization treatment to obtain a hard carbon negative electrode material.

[0016] The embodiment of the present invention provides a method for preparing a hard carbon negative electrode material, which comprises: using starch as a raw material, subjecting starch particles to a two-stage crosslinking pretreatment to obtain crosslinked starch particles, wherein the two-stage crosslinking treatment can effectively control the degree of starch crosslinking so that the crosslinked starch has appropriate pores, and then performing a carbonization treatment to obtain a hard carbon negative electrode material.

[0017] In an optional embodiment, the starch granules are subjected to a two-stage crosslinking pretreatment, comprising: mixing the starch granules with a first crosslinking agent and then subjecting them to a first-stage crosslinking treatment, and then mixing the starch granules subjected to the first-stage crosslinking treatment with a second crosslinking agent and then subjecting them to a second-stage crosslinking treatment, wherein:

[0018] The first cross-linking agent is selected from at least one of phosphate, pyrophosphate, sulfate and maleic anhydride; the second cross-linking agent is selected from polybasic organic acid with hydroxyl group;

[0019] Preferably, the amount of the first cross-linking agent is 5%-25% of the total mass of the raw starch particles;

[0020] Preferably, the amount of the second cross-linking agent is 5%-15% of the total mass of the raw starch particles.

[0021] The preparation method of the hard carbon negative electrode material provided by the embodiment of the present invention uses starch as raw material, and obtains cross-linked starch particles by pre-treating starch particles by two-stage cross-linking. In this process, the type and amount of the first cross-linking are controlled to control the degree of starch cross-linking, so that the starch skeleton can achieve a semi-fixed state, which can not only maintain the original morphology of the starch, but also give the second cross-linking a certain shrinkage space, and then treat it with a second cross-linking agent to shrink the pore structure of the starch, so as to achieve the purpose of adjusting the pores, and finely regulate the pore structure of the starch-based hard carbon, so as to obtain better sodium storage performance, and obtain a hard carbon negative electrode material with both high capacity and high first efficiency. If the second cross-linking agent is directly used for a first cross-linking, the pore structure will shrink excessively, and the original morphology of the starch cannot be maintained, so that the performance of the prepared hard carbon negative electrode material is deteriorated, which is not conducive to the insertion and removal of sodium ions.

[0022] In an optional embodiment, the first cross-linking treatment is: after the starch particles are solid-phase mixed with the first cross-linking agent, heating treatment is performed in an inert gas atmosphere;

[0023] Preferably, the first cross-linking agent includes at least one of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, ammonium pyrophosphate, ammonium sulfate, ammonium hydrogen sulfate and maleic anhydride, more preferably at least one of diammonium phosphate and maleic anhydride;

[0024] Preferably, the particle size of the first cross-linking agent is less than 100 μm, which can make the solid phase mixing more uniform.

[0025] Preferably, the crosslinking reaction temperature of the first-stage crosslinking treatment is 80-300° C., the crosslinking reaction time is 3-36 hours, and the inert gas atmosphere is any one of nitrogen and argon.

[0026] The preparation method of the hard carbon negative electrode material provided in the embodiment of the present invention uses starch as raw material, first mixes starch particles with a first crosslinking agent, and then heats and performs a crosslinking treatment. The first crosslinking agent has the following characteristics: after the starch particles are crosslinked for a period of time, the starch can be carbonized to maintain its original particle morphology and natural pore structure. It can be seen that the embodiment of the present invention uses the first crosslinking agent to perform a crosslinking treatment on the starch particles, which can fully activate the starch molecular chains, achieve full penetration of the first crosslinking agent into the starch particles and the initial crosslinking of the starch molecular chains, and control the crosslinking temperature and time during the crosslinking process, so as to control the degree of crosslinking and provide a certain shrinkage space for the second crosslinking.

[0027] In an optional embodiment, the two-stage crosslinking treatment is: after the starch granules subjected to the first-stage crosslinking treatment are solid-phase mixed with the second crosslinking agent, heating treatment is performed in an inert gas atmosphere;

[0028] Preferably, the second cross-linking agent comprises at least one of citric acid, malic acid, tartaric acid, 2-hydroxyglutaric acid, 3-hydroxyglutaric acid, glucaric acid, mucic acid and 3-hydroxy-3-methylglutamic acid, more preferably at least one of citric acid and tartaric acid;

[0029] Preferably, the crosslinking reaction temperature of the second-stage crosslinking treatment is 120-300° C., the crosslinking reaction time is 3-36 hours, and the inert gas atmosphere is any one of nitrogen and argon.

[0030] The preparation method of the hard carbon negative electrode material provided in the embodiment of the present invention uses starch as a raw material, first uses a first crosslinking agent to perform a first-stage crosslinking treatment on starch particles, and then uses a second crosslinking agent to perform a second-stage crosslinking treatment on the starch particles obtained by the first-stage crosslinking treatment. The second crosslinking agent has the following characteristics: after the starch particles are subjected to the second-stage crosslinking treatment, they are carbonized, the starch particles melt and agglomerate but do not expand, and the natural pore structure of the starch particles shrinks. It can be seen that the embodiment of the present invention uses a second crosslinking agent to perform a second-stage crosslinking treatment on the starch particles subjected to the first-stage crosslinking treatment, so as to achieve the deep crosslinking of the starch molecular chain and achieve the purpose of finely adjusting the pore structure. The second crosslinking agent is selected from a polyacid with a hydroxyl group, and the polyacid with a hydroxyl group can achieve the purpose of shrinking the pores, while the polyacids of oxalic acid, isophthalic acid, and succinic acid cannot achieve the purpose of adjusting the pores. In addition, the appropriate amount of the second crosslinking agent, the temperature and time of the second-stage crosslinking, etc. are beneficial for finely adjusting the pore structure and improving the thermal stability of the starch particles. If the amount of the second crosslinking agent is too much, the starch particles shrink excessively, and most of the pores are closed, which is not conducive to the insertion and removal of sodium ions.

[0031] In an optional embodiment, the carbonization treatment includes: pre-carbonizing and crushing the cross-linked starch particles obtained by the two-stage cross-linking pre-treatment, and then performing a high-temperature heat treatment to obtain a hard carbon negative electrode material;

[0032] Preferably, the temperature of the pre-carbonization treatment is 400-900°C, the heating rate is 1-5°C / min, the time is 1-6h, and the reaction atmosphere is any one of nitrogen, argon, and helium;

[0033] Preferably, the crushing makes the material particle size distribution as follows: D10: 0.5-3 μm, D50: 4-12 μm; D90: 7-12 μm, more preferably, the particle size distribution is as follows: D10: 1-2 μm; D50: 5-7 μm; D90: 8-10 μm;

[0034] Preferably, the temperature of the high temperature heat treatment is 1000-1600° C., the heating rate is 1-5° C. / min, the time is 30 min-12 h, and the reaction atmosphere is any one of nitrogen and argon.

[0035] The preparation method of the hard carbon negative electrode material provided in an embodiment of the present invention pre-carbonizes and crushes the cross-linked starch particles obtained by two-stage cross-linking pretreatment, and then performs high-temperature heat treatment. The pre-carbonization and high-temperature heat treatment can effectively improve the structural order of the hard carbon material, reduce some irreversible defects, enrich the pore structure and enhance the storage capacity of sodium ions, and finally obtain the hard carbon negative electrode material.

[0036] In an optional embodiment, the starch includes one or more of natural starch and modified starch;

[0037] Preferably, the natural starch comprises at least one of corn starch, potato starch, wheat starch, rice starch, pea starch, tapioca starch and sweet potato starch;

[0038] Preferably, the modified starch comprises at least one of oxidized starch, pregelatinized starch, cationic starch and phosphate starch;

[0039] Preferably, the starch granules have a particle size of 3-100 μm.

[0040] In the second aspect, an embodiment of the present invention also provides a hard carbon negative electrode material prepared by the above-mentioned preparation method, wherein the hard carbon negative electrode material has abundant nanopores, and the nanopores are composed of open channels and closed channels, and the pore diameters of the open channels and the closed channels are both 0.8-2.5nm, and the pore diameter of the open channels is ≤0.4nm.

[0041] An embodiment of the present invention provides a hard carbon negative electrode material, which has abundant nanopores, and the nanopores are composed of open channels and closed channels, and the pore diameters of the open channels and the closed channels are both 0.8-2.5nm, and the sodium is stored in the pores in the form of sodium metal clusters. If the pores are too small, the sodium storage capacity provided is limited, and if the pores are too large, the sodium metal clusters formed in the pores are too large, and the reversibility of the sodium storage capacity provided by the pores cannot be ensured; at the same time, the pore diameter of the open channels is ≤0.4nm, and if the pore openings of the open pores are too large, the solvent molecules on the solvated sodium ions cannot be removed, causing the SEI film to grow in the open pores, thereby reducing the first effect.

[0042] In an optional embodiment, the interlayer spacing of the hard carbon negative electrode material is greater than 0.36 nm; the specific surface area of ​​the hard carbon negative electrode material measured by nitrogen at 77 K is less than 10 m 2 / g; the specific surface area of ​​hard carbon anode material measured by carbon dioxide at 273K is ≤120m 2 / g; the specific surface area of ​​the hard carbon negative electrode material obtained by small-angle X-ray scattering test is 200-600m 2 / g. The kinetic diameter of nitrogen molecules at 77K is about 0.37 nanometers, and nitrogen adsorption-desorption tests are basically unable to detect open pores with pore openings less than 0.4 nanometers, while the kinetic diameter of carbon dioxide at 273K is about 0.33 nanometers, and some open pores with pore openings less than 0.4 nanometers can be detected. Therefore, if the specific surface area obtained by the carbon dioxide adsorption-desorption test is larger than the specific surface area obtained by the nitrogen adsorption-desorption test, it indicates that there are a large number of open pores with pore openings less than 0.4 nanometers in the sample. The specific surface area obtained by the small-angle X-ray diffraction test includes the contribution of closed pores and open pores to the specific surface area of ​​the sample. Therefore, if the specific surface area measured by the small-angle X-ray scattering is much larger than the specific surface area measured by the carbon dioxide adsorption-desorption test, it indicates that there are a large number of closed pores in the sample.

[0043] The hard carbon negative electrode material provided by the embodiment of the present invention has an interlayer spacing greater than 0.36nm. If the interlayer spacing is less than 0.36nm, sodium ions cannot be freely embedded in and out of the hard carbon layers. The specific surface area is not higher than 10m 2 / g, too high specific surface area will cause the formation of a large amount of SEI, thereby reducing the first coulombic efficiency.

[0044] In an optional embodiment, the reversible capacity of the hard carbon negative electrode material is 280-340 mAh / g, and the first efficiency is 80-93%.

[0045] In a third aspect, an embodiment of the present invention further provides a sodium ion battery, wherein the negative electrode of the sodium ion battery comprises the above-mentioned hard carbon negative electrode material.

[0046] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0047] Example 1

[0048] A method for preparing a hard carbon negative electrode material comprises the following steps:

[0049] The raw material is starch particles with a particle size of 3-100 microns, including natural starches such as corn starch, potato starch, wheat starch, rice starch, pea starch, cassava starch, sweet potato starch, and one or more of modified starches such as oxidized starch, pregelatinized starch, cationic starch, and phosphate starch. If the starch is directly carbonized without cross-linking treatment, the starch will swell and destroy its natural structure, resulting in the destruction of its natural pore structure.

[0050] The preparation method comprises the following steps:

[0051] S1: corn starch is used as raw material, the particle size of starch particles is 3-100 microns, and the first type of cross-linking agent is crushed to make its particle size less than 100 μm. Then the starch particles are solid-phase mixed with the first cross-linking agent, and the first cross-linking agent accounts for 5% of the total mass of the starch particles.

[0052] S2: Perform the first cross-linking treatment, the cross-linking reaction temperature is 170° C., the cross-linking time is 4 hours, and the reaction atmosphere is a non-oxidizing atmosphere such as nitrogen and argon.

[0053] S3: The starch granules treated with the first cross-linking treatment are solid-phase mixed with the second cross-linking agent and subjected to the second-stage treatment, wherein the second cross-linking agent accounts for 5% of the total mass of the starch granules treated with the first cross-linking treatment, and the second-stage cross-linking temperature is 160° C. and the time is 4 hours.

[0054] S4: Pre-carbonizing the cross-linked starch granules to obtain a pre-carbonized product. The pre-carbonization temperature is 500°C, the heating rate is 1-5°C / min, the insulation time is 3h, and the reaction atmosphere is a non-oxidizing atmosphere such as nitrogen, argon, and helium.

[0055] S5: The pre-carbonized product is crushed to obtain the desired particle size, and the particle size parameters are as follows: D10: 0.5-3μm, D50: 4-12μm; D90: 7-12μm.

[0056] S6: The crushed pre-carbonized product is subjected to high-temperature heat treatment to obtain finished hard carbon. The heat treatment temperature is 1000°C, the heating rate is 1-5°C / minute, the heat treatment time is 2h, and the reaction atmosphere is a non-oxidizing atmosphere such as nitrogen and argon.

[0057] The steps for preparing the hard carbon negative electrode materials in Examples 2-11 and Comparative Examples 1-10 are the same as those in Example 1, and the experimental parameters are shown in Table 1 below:

[0058] Table 1

[0059]

[0060]

[0061] Note: The dosage of the first cross-linking agent is the percentage of the first cross-linking agent in the total mass of starch granules; the dosage of the second cross-linking agent is the percentage of the second cross-linking agent in the total mass of raw starch granules.

[0062] The hard carbon samples obtained in the examples and comparative examples are subjected to nitrogen adsorption and desorption, carbon dioxide adsorption and desorption, and small-angle X-ray scattering tests to obtain the pore structure information of the samples. By combining the results of the nitrogen adsorption and desorption tests and the carbon dioxide adsorption and desorption tests, the open pore information of the hard carbon samples with pore openings below 0.4 nanometers can be obtained. By combining the above three tests, the closed pore information of the samples can be obtained. At the same time, the hard carbon samples that have not been crushed in Example 3 are subjected to scanning electron microscopy analysis. The SEM photos are shown in Figure 1 ,from Figure 1 It can be seen that after the two-stage cross-linking treatment, the starch granules have undergone a certain degree of melting. Figure 2 It can be seen that the charge and discharge curve of the hard carbon sample consists of obvious slope area and platform area. The platform area contributes most of the capacity. It is generally believed that the capacity of the platform area comes from the filling of sodium metal clusters in the nanopores, indicating that there are a large number of nanopores in the hard carbon sample.

[0063] The hard carbon negative electrode samples prepared in the embodiments and comparative examples were mixed with CMC, SBR, and Super P conductive carbon black in a mass ratio of 94.5:1.5:2.5:1.5 to form a slurry with a solid content of 43%. The slurry was then evenly scraped onto the current collector copper foil. After drying, the pole pieces were cut. The button cell was assembled in a glove box with an Ar atmosphere, using metallic sodium as the counter electrode and a 1MNaPF6 (the volume ratio of ethylene carbonate to diethyl carbonate is 1:1) solution as the electrolyte to assemble a CR2032 battery. The obtained battery was tested for the sodium storage performance of the hard carbon negative electrode according to the following test steps: 0.05C constant current discharge to 0V, 50μA constant current discharge to 0V, 10μA constant current discharge to 0V, 0.05C constant current charge to 2V, and cycled for two weeks. The test results are shown in Table 2 below:

[0064] Table 2

[0065]

[0066]

[0067] By analyzing the experimental data in the above table, it can be seen that: compared with Examples 1-5, only the first cross-linking agent is used to cross-link the starch in Examples 1-5. Although a very high sodium embedding capacity can be obtained, the first efficiency of the corresponding hard carbon sample is low. In Examples 1-5, the addition of the second cross-linking agent effectively modulates the pore structure of the hard carbon sample, reduces its specific surface area, and thus improves the first efficiency. Examples 6 and 7 show that maleic anhydride and ammonium sulfate can achieve similar effects to diammonium phosphate, but the sodium storage performance of the obtained hard carbon samples is lower than that of diammonium phosphate. The results of Examples 8 and 9 show that tartaric acid and malic acid can obtain a pore shrinkage effect similar to that of citric acid. The results of Examples 10 and 11 show that when rice starch and potato starch are used as raw materials and a two-stage cross-linking treatment is adopted, the resulting product can also obtain relatively excellent sodium storage performance. In Comparative Example 6, the amount of the first type of cross-linking agent reached 30%, and the performance of the obtained hard carbon was poor. Comparative Example 7 adds a second type of cross-linking agent on the basis of Comparative Example 6. It can be seen that the performance of the hard carbon obtained is similar to that of Comparative Example 6, indicating that the addition of the second cross-linking agent at this time can no longer regulate the pore structure of the hard carbon. Compared with Example 3, an excessive amount of the second cross-linking agent is added in Comparative Example 8. The sodium storage performance of the hard carbon sample obtained in Comparative Example 8 is significantly lower than that of Example 3. The CO2 adsorption and desorption test and the small-angle X-ray scattering test show that the open pores and closed pores of Comparative Example 8 are significantly lower than those of Example 3, indicating that adding too much second cross-linking agent will cause excessive collapse of the pore structure, thereby causing a decrease in sodium storage performance. Comparative Example 9 shows that the sodium storage performance of the hard carbon sample obtained by adding only the second cross-linking agent is poor. The pore structure analysis shows that the use of only the second cross-linking agent will cause the pore structure of the starch granules to shrink excessively, resulting in poor performance of the prepared hard carbon. Comparative Example 10 shows that exchanging the order of the first cross-linking agent and the second cross-linking agent will cause a significant decrease in the performance of the prepared hard carbon, because cross-linking with the second cross-linking agent first will cause excessive shrinkage of the pore structure.

[0068] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon negative electrode material, characterized in that: include: Using starch as raw material, starch particles are subjected to two-stage cross-linking pretreatment and then carbonized to obtain hard carbon negative electrode materials.

2. The preparation method according to claim 1, characterized in that: The starch granules are subjected to a two-stage crosslinking pretreatment, comprising: mixing the starch granules with a first crosslinking agent and then subjecting them to a first-stage crosslinking treatment, and then mixing the starch granules subjected to the first-stage crosslinking treatment with a second crosslinking agent and then subjecting them to a second-stage crosslinking treatment, wherein: The first cross-linking agent is selected from at least one of phosphate, pyrophosphate, sulfate and maleic anhydride; the second cross-linking agent is selected from polybasic organic acid with hydroxyl group; Preferably, the amount of the first cross-linking agent is 5%-25% of the total mass of the raw starch particles; Preferably, the amount of the second cross-linking agent is 5%-15% of the total mass of the raw starch particles.

3. The preparation method according to claim 2, characterized in that: The first cross-linking treatment comprises: mixing starch particles with the first cross-linking agent in a solid phase, and then heating the mixture in an inert gas atmosphere; Preferably, the first cross-linking agent includes at least one of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, ammonium pyrophosphate, ammonium sulfate, ammonium hydrogen sulfate and maleic anhydride, more preferably at least one of diammonium phosphate and maleic anhydride; Preferably, the particle size of the first cross-linking agent is less than 100 μm; Preferably, the crosslinking reaction temperature of the first crosslinking treatment is 80-300°C, and the crosslinking reaction time is 3-36h; Preferably, the inert gas atmosphere is any one of nitrogen and argon.

4. The preparation method according to claim 2, characterized in that: The second-stage crosslinking treatment comprises: mixing the starch granules subjected to the first-stage crosslinking treatment with the second crosslinking agent in a solid phase, and then heating the mixture in an inert gas atmosphere; Preferably, the second cross-linking agent comprises at least one of citric acid, malic acid, tartaric acid, 2-hydroxyglutaric acid, 3-hydroxyglutaric acid, glucaric acid, mucic acid and 3-hydroxy-3-methylglutamic acid, more preferably at least one of citric acid and tartaric acid; Preferably, the crosslinking reaction temperature of the second-stage crosslinking treatment is 120-300°C, and the crosslinking reaction time is 3-36h; Preferably, the inert gas atmosphere is any one of nitrogen and argon.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The carbonization treatment comprises: pre-carbonizing and crushing the cross-linked starch particles obtained by the two-stage cross-linking pre-treatment, and then performing a high-temperature heat treatment to obtain the hard carbon negative electrode material; Preferably, the temperature of the pre-carbonization treatment is 400-900°C, the heating rate is 1-5°C / min, the time is 1-6h, and the reaction atmosphere is any one of nitrogen, argon and helium; Preferably, the crushing makes the material particle size distribution as follows: D10: 0.5-3 μm, D50: 4-12 μm; D90: 7-12 μm, more preferably, the particle size distribution is as follows: D10: 1-2 μm; D50: 5-7 μm; D90: 8-10 μm; Preferably, the temperature of the high temperature heat treatment is 1000-1600° C., the heating rate is 1-5° C. / min, the time is 30 min-12 h, and the reaction atmosphere is any one of nitrogen and argon.

6. The preparation method according to any one of claims 1 to 4, characterized in that: The starch includes one or more of natural starch and modified starch; Preferably, the natural starch comprises at least one of corn starch, potato starch, wheat starch, rice starch, pea starch, tapioca starch and sweet potato starch; Preferably, the modified starch comprises at least one of oxidized starch, pregelatinized starch, cationic starch and phosphate starch; Preferably, the starch granules have a particle size of 3-100 μm.

7. A hard carbon negative electrode material, characterized in that: The hard carbon negative electrode material has abundant nanopores, and the nanopores are composed of open pores and closed pores. The pore diameters of the open pores and the closed pores are both 0.8-2.5 nm, and the pore diameter of the open pores is ≤0.4 nm.

8. The hard carbon negative electrode material according to claim 7, characterized in that: The interlayer spacing of the hard carbon negative electrode material is greater than 0.36 nm; the specific surface area of ​​the hard carbon negative electrode material measured by nitrogen at 77 K is less than 10 m 2 / g; the specific surface area of ​​the hard carbon negative electrode material measured by carbon dioxide at 273K is ≤120m 2 / g; the specific surface area of ​​the hard carbon negative electrode material obtained by small-angle X-ray scattering test is 200 to 600m 2 / g.

9. The hard carbon negative electrode material according to claim 7, characterized in that: The reversible capacity of the hard carbon negative electrode material is 280-340 mAh / g, and the first efficiency is 80-93%.

10. A sodium ion battery, characterized in that: The sodium ion battery negative electrode comprises a hard carbon negative electrode material prepared by the preparation method described in any one of claims 1 to 6 or a hard carbon negative electrode material described in any one of claims 7 to 9.

Citation Information

Patent Citations

  • Preparation method of crosslinked starch

    CN107964050A

  • Preparation method of starch-based hard carbon negative electrode material, negative electrode material and sodium ion battery

    CN115536002A

  • Hard carbon negative electrode material, preparation method thereof and secondary battery

    CN115838165A

  • Preparation method of sodium ion battery hard carbon negative electrode material

    CN116395670A

  • Lithium ion secondary battery soft carbon anode material, method of manufacturing the same, and lithium ion secondary battery

    JP2015128045A

Cited By

  • Iron-selenium double-monatomic nitrogen-doped carbon-based composite material as well as preparation method and application thereof

    CN120955099A